A/2-b/3=1 solve for a, add b/3 to both sides
a/2=1+b/3 which is equal to
a/2=(3+b)/3 multiply both sides by 2
a=(6+2b)/3 now you can substitute this into 2a+3b giving you:
2(6+2b)/3 + 3b which is equal to
(12+4b+9b)/3
(13b+12)/3
Answer:
It should I only looked at the first few columns and the matched up
Step-by-step explanation:
Affect the size, shape, or phase of a substance.
Answer:
1Step-by-step explanation:
We collect like terms
8x - 3x = 3 + 5 + 9
This is bcos if a (-) sign crosses the equals sign it becomes a (+), and if a (+) sign crosses the equals sign it becomes (-)
We the have
5x = 17
Divide both sides by 5
x = 17/5
x = 3.4